Corporate litigation and executive turnover - Aharony, Joseph; Liu, Chelsea; Yawson, Alfred (Journal of corporate finance (Amsterdam, Netherlands), 2015)
We examine executive turnover following environmental, antitrust, intellectual property (IP), and contractual lawsuits filed against their companies. We find that companies' responses to lawsuits depend on the nature of the allegations. In particular, contractual lawsuits are followed by increased turnover of CEOs and inside directors, whereas following environmental and IP lawsuits, only outside directors tend to depart. Antitrust lawsuits are followed by increased appointments of inside directors. We also find that lawsuit merit and pecuniary demands for damages play a role in determining executive turnover. In addition, we find some evidence of reduced CEO compensation following lawsuits. Overall, we provide insights into the effectiveness of the executive labor market in responding to alleged corporate wrongdoing. •Does CEO and director turnover increase with encounters of corporate lawsuits?•Corporate attitudes differ depending on the nature of allegation and lawsuit merit.•CEO and inside director turnover increases following contractual lawsuits•Following environmental lawsuits only outside directors tend to depart.•Reduction in CEO compensation occurs following contractual lawsuits.